HADITS INFORMATION ABOUT HELPING (COMPLETING) WITH SOMETHING HAPPENED IN THE SOCIETY - Rayana, Jagat (International Journal of Islamic Khazanah, 2020)
Today, begging and begging for something that is considered normal is mainly used as a livelihood to meet their needs. This phenomenon continues to develop and has tools that can support its development. This study aims to look at the hadiths about begging and see the implications on social order, with content analysis methods and qualitative data type takhrij methods, namely data relating to authenticity, blasphemy, content and implications of Hadith begging. The main source of data is the books of the Hadith al-Mashhadi al-Ashliyah assisted with supporting data sources that produce the Hadith about begging, namely marfu ’Qauli haqiqi due to the words of Rasulallah SAW and including the Hadith ahad Mashhur because the raw is four at the beginning of thabaqah and subsequently accompanied by several narrators. The hadith asks for clear whereabouts and as a strict rebuke to all creatures of Allah SWT to avoid begging and encourage hard work and earn a living that is lawful to meet all their needs.